Museum as a place of informal learning - Brajčić, Marija (Revija za elementarno izobraževanje, 2022)
Museum pedagogy is a museological and pedagogical discipline that deals with communication between artifacts and the public, and the interpretation of cultural heritage content to satisfy cognitive and experiential interests while accepting cultural and civilizational achievements. This paper discusses theoretical knowledge about the nature of learning in the context of the modern division into formal, non-formal, and informal learning. The research includes the museum as a place of non-formal and informal learning and analyses indicators of visitor engagement. The research was conducted among students of the Faculty of Humanities and Social Sciences in Split.
Keywords: engagement indicators; formal learning; formalno; kazalniki angažiranosti; museum; muzej; neformalno in priložnostno učenje; nonformal and informal learning; students; študenti